Flexible ultraviolet photodetector based ZnO film sputtered on paper. (February 2020) - Li, Huixin; Huang, Jin; Zheng, Qinghong; Zheng, Yilin
Abstract: ZnO thin films were deposited on paper substrates by radio frequency magnetron sputtering at room temperature. By appropriate controlling the sputtering pressure, highly oriented (002) ZnO film with large grain size and low defect density can be obtained. Metal-semiconductor-metal structure ultraviolet photodetectors (UVPDs) were fabricated based on the ZnO/paper films and their optoelectronic response properties were investigated in detail. The optimum UVPD exhibits high UV sensitivity, showing peak responsivity at 380 nm. At applied voltage of 10 V, the UVPD has a high responsivity of 0.86 A/W and a high on/off ratio of ~600. Moreover, the flexible UVPD exhibits excellent stability and reproducibility under different bending conditions. The high flexibility of the UVPD was attributed to the compact and continuous properties of the sputtered film. The excellent operating characteristics make the UVPD a potential candidate for wearable UV meters and communication devices. Highlights: Paper based ultraviolet photodetector exhibits high flexibility and stability. The paper substrate is renewable, biodegradable and abundant. ZnO film was grown on paper at room temperature by magnetron sputtering. Highly oriented (002) ZnO film was prepared with appropriate sputtering pressure.